Efficacy and safety of racecadotril as an adjunct to oral rehydration therapy for acute watery diarrhea in children - Sreenivas, S K; Lakshmi, M; Pavitra, N A (Indian Journal of Child Health, 2016)
Background: Racecadotril, an enkephalinase inhibitor with antisecretory action is a safe and effective treatment for acute diarrhea for children and adults. As an adjunct to oral rehydration therapy (ORT) in Indian children, its efficacy and safety data are scarce. Methods: A total of 117 children with acute watery diarrhea for not more than 7 days were randomized into two groups. Group A (control group) received ORT and zinc only while Group B (study group) received a combination of racecadotril (1.5 mg/kg q8 h), zinc and ORT. Primary end point was the number of loose stools during first 48 h of treatment. Time to cure as well as total volume of oral rehydration solution (ORS) consumed was also measured. Results: Baseline characteristics were not significantly different between the groups. Mean 48 h stool frequency in the study group was 10.47±3.2 episodes and that in control group was 15.87±4.6 episodes indicating a significant reduction of 34.1% with racecadotril (p=0.00016). The mean time for recovery in the study group was 37.98±6.1 h and 51.02±9.4 h in control group indicating a significant reduction of 25.6% with racecadotril (p=0.002). The mean volume of ORS consumed before recovery in the study group was 162.72 ml as compared to 232.68 ml in control group pointing to a significant reduction of 30.1% in the study group. Conclusions: Racecadotril is effective as an adjunct to ORT and early continued feeding in infants and children with acute watery diarrhea.